REKAYASA NILAI HARGA PEMBUATAN TERHADAP EFEKTIFITAS PENGGUNAAN BAHAN PADA PEMBANGUNAN PERUMAHAN TIRTO PENATARAN ASRI TIPE 70/135 KECAMATAN NGLEGOK KABUPATEN BLITAR - Ma'ruf, Mochamad Tamim (Universitas Islam Balitar Blitar, 2017)
One-solving methods and techniques necessary to avoid inefficiencies and not economic costs as well as reduce the cost of housing construction is the method of Value Engineering. Value engineering is a method and cost control techniques to analyze a function to its value at the lowest cost alternative (most economical) without reducing the quality desired.At the writing of this study used a comparison method by comparing the initial design to the design proposal of the author. In the housing projects Upgrading Tirto Penataran Asri type 70, the application of Value Engineering conducted on the job a couple walls and roofs pair by replacing some work items with a more economical alternative but does not change the original function and high aesthetic level and still qualify safe. For that performed the step of determining a work item, the alternative stage, the analysis stage, and the stage of recommendations to get a Value Engineering application and cost savings against the wall a couple of work items and partner roof.The proposed design as compared to the initial design. Work items discussed was the work of a couple wall having analyzed obtained savings of Rp. 2,747,643.56 and the work of the roof pair obtained savings of Rp. 2,363,446.80. Thus the total overall savings gained is Rp 5,111,090.36 or savings of 0048%.